The Same Story All Over Again? - Daniel Nascimento (Carthaginensia, 2022)
In this article, a comparative reading of the two “Meribah narratives” of the Pentateuch is made, analysing the specificities of each one and the different theological claims made by these two episodes, one in Exod 17,1-7, the other in Num 20,1-13. For achieving this goal, narrative criticism is a useful tool, particularly the categories of “plot” and “theme”. A thorough comparison between these two miraculous episodes, in which Moses provides water to the thirsty Israelites from a rock in the wilderness, will show that the theological issues of the presence of God between his people and the unveiling of His holiness are the key points in each of these episodes.